2022
DOI: 10.1515/jbcpp-2022-0060
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of endurance exercise as a growth hormone mediator in adolescent women’s

Abstract: Objectives Overweight status decreases the growth hormone (GH) secretion, thus, increasing the risk factors for medical complications. However, proper exercise is reported to enhance GH and affect the energy balance. Therefore, exercise is proclaimed to be an accurate and engaging therapy to increase GH in preventing overweight. This study aims to investigate the physiological response of exercise in mediating the increase of GH secretion in female adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Exercise is also known to prevent deficiency of GH secretion in overweight and obese individuals (Al-Samerria & Radovick, 2021). This finding was supported by research conducted by Sugiharto, Merawati, Pranoto, & Susanto (2022), which demonstrated that a single session of endurance training at an intensity of 60-70% HR max performed for 30-35 minutes on a treadmill increased GH secretion in obese women. Research conducted by Berry, Hubal, & Wideman (2018) also reported that treadmill exercise in moderate intensity performed for 60 minutes increased the release of GH levels in healthy and prediabetic subjects with obesity (BMI = 32.1±4.0 kg/m 2 ).…”
Section: Introductionmentioning
confidence: 81%
“…Exercise is also known to prevent deficiency of GH secretion in overweight and obese individuals (Al-Samerria & Radovick, 2021). This finding was supported by research conducted by Sugiharto, Merawati, Pranoto, & Susanto (2022), which demonstrated that a single session of endurance training at an intensity of 60-70% HR max performed for 30-35 minutes on a treadmill increased GH secretion in obese women. Research conducted by Berry, Hubal, & Wideman (2018) also reported that treadmill exercise in moderate intensity performed for 60 minutes increased the release of GH levels in healthy and prediabetic subjects with obesity (BMI = 32.1±4.0 kg/m 2 ).…”
Section: Introductionmentioning
confidence: 81%
“…Due to the increased maximum oxygen volume (VO 2 max), exercise increases the expression of glucose transporter type 4 (GLUT4) in cell membranes, improving insulin sensitivity by 25–50% and helping in maintaining normal blood glucose levels [ 57 ]. Therefore, exercise can be one of the pillars of lifestyle modification in individuals with obesity [ 21 , 45 ]. Regular exercise can reduce stenosis in coronary arteries by increasing nitric oxide (NO) and endothelial nitric oxide synthase (eNOS) production, and increasing anti-inflammatory cytokines in the vascular endothelium [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the onset of obesity often occurs in the young population, and this population will likely suffer from more extended morbidity [ 19 ]. An unhealthy diet and lack of physical activity lead to obesity [ 6 , 20 , 21 ]. Through their anti-inflammatory effects, lifestyle changes using an exercise-based non-pharmacological approach are considered effective in preventing increased morbidity [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Music player 5 headphones (MP5) is used to listen to music during exercise (Jia et al, 2016). Heating and cooling were each performed for 5 min with light intensity (50-60% HR max ) (Rejeki et al, 2022;Sugiharto et al, 2023). Maximum heart rate prediction was carried out using the 220-age (in years) formulation (Sugiharto et al, 2021;Murphy et al, 2019).…”
Section: Exercise Protocolmentioning
confidence: 99%